Identification of Two Critical Neutralizing Epitopes in the Receptor Binding Domain of Hepatitis B Virus preS1 - Yato, Keigo; Onodera, Taishi; Matsuda, Mami; Moriyama, Saya; Fujimoto, Akira; Watashi, Koichi; Aizaki, Hideki; Tanaka, Tomohisa; Moriishi, Kohji; Nishitsuji, Hironori; Shimotohno, Kunitada; Tamura, Koji; et al. (Journal of virology, 2021)
The HBV preS1 amino acid 2 to 47 region (preS1/2–47) is essential for virus binding to sodium taurocholate cotransporting polypeptide. Several MAbs targeting preS1/2–47 have been reported to neutralize HBV infection; however, which region in preS1/2–47 contains the critical neutralizing epitope(s) for HBV infection is unclear. Hepatitis B virus (HBV) infection is a major public health problem. Human hepatocytes are infected with HBV via binding between the preS1 region in the large envelope protein of HBV and sodium taurocholate cotransporting polypeptide. Although several monoclonal antibodies (MAbs) that recognize the receptor binding domain in preS1 and neutralize HBV infection have been isolated, details of neutralizing epitopes are not understood. In this study, we generated 13 MAbs targeting the preS1 receptor binding domain from preS1-specific memory B cells derived from DNA-immunized mice. The MAbs were classified into three groups according to the epitope regions, designated epitopes I to III. A virus neutralization assay revealed that MAbs recognizing epitopes I and III neutralized HBV infection, suggesting that these domains are critical epitopes for viral neutralization. In addition, a neutralization assay against multiple genotypes of HBV revealed that epitope I is a semipangenotypic neutralizing epitope, whereas epitope III is a genotype-specific epitope. We also showed that neutralizing MAbs against preS1 could neutralize HBV bearing a vaccine-induced escape mutation. These findings provide insight into novel immunoprophylaxis for the prevention and treatment of HBV infection. IMPORTANCE The HBV preS1 amino acid 2 to 47 region (preS1/2–47) is essential for virus binding to sodium taurocholate cotransporting polypeptide. Several MAbs targeting preS1/2–47 have been reported to neutralize HBV infection; however, which region in preS1/2–47 contains the critical neutralizing epitope(s) for HBV infection is unclear. Here, we generated several MAbs targeting preS1/2–47, and we found that MAbs recognizing the N or C terminus of preS1/2–47 remarkably neutralized HBV infection. We further confirmed the neutralizing activity of anti-preS1 MAbs against HBV with a vaccine escape mutation. These data clarified the relationship between the antibody epitope and the virus-neutralizing activity and also suggested the potential ability of a vaccine antigen containing the preS1 region to overcome the weakness of current hepatitis B vaccines comprising the small S protein.